Evaluation of different types of stimuli in an Event-Related Potential-based Brain–Computer Interface Speller under Rapid Serial Visual Presentation - Ron-Angevin, Ricardo; Fernández-Rodríguez, Álvaro; Velasco-Álvarez, Francisco Javier; Lespinet-Najib, Véronique; André, Jean-Marc (MDPI, 2024)
Rapid serial visual presentation (RSVP) is currently a suitable gaze-independent paradigm for controlling visual brain–computer interfaces (BCIs) based on event-related potentials (ERPs), especially for users with limited eye movement control. However, unlike gaze-dependent paradigms, gaze-independent ones have received less attention concerning the specific choice of visual stimuli that are used. In gaze-dependent BCIs, images of faces—particularly those tinted red—have been shown to be effective stimuli. This study aims to evaluate whether the colour of faces used as visual stimuli influences ERP-BCI performance under RSVP. Fifteen participants tested four conditions that varied only in the visual stimulus used: grey letters (GL), red famous faces with letters (RFF), green famous faces with letters (GFF), and blue famous faces with letters (BFF). The results indicated significant accuracy differences only between the GL and GFF conditions, unlike prior gaze-dependent studies. Additionally, GL achieved higher comfort ratings compared with other face-related conditions. This study highlights that the choice of stimulus type impacts both performance and user comfort, suggesting implications for future ERP-BCI designs for users requiring gaze-independent systems.
Keywords: Redes neuronales (Informática); Medicina - Proceso de datos; Brain-computer interface (BCI); Event-related potential (ERP); rapid visual serial presentation (RSVP); Stimulus; Speller